2005
DOI: 10.1002/lt.20430
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved iliac artery is indispensable interposition graft material for middle hepatic vein reconstruction of right liver grafts

Abstract: Cryopreserved iliac vein grafts (IVGs) have often been used for reconstruction of middle hepatic vein (MHV) branches in right liver grafts, but their storage pool has often been exhausted in our institution due to the low incidence of deceased donor organ procurement. To overcome this shortage of IVG, we started to use cryopreserved iliac artery graft (IAG). During September and October 2004, we carried out 41 cases of adult living donor liver transplantation, including 29 right lobe grafts with MHV reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
97
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 11 publications
(14 reference statements)
1
97
0
Order By: Relevance
“…Wide ostium drainage models have been developed to accept the graft's compression. 2,11 Hwang and associates, [12][13][14] who advocated that SVHs should be greater than 5 mm to be integrated into the drainage system, reported in their latest study that they integrated SVHs ≥ 4 mm into the drainage system. Most the integration models aimed at developing a wide ostium anastomosis tolerating compression are made of allogenic grafts or artificial graft materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wide ostium drainage models have been developed to accept the graft's compression. 2,11 Hwang and associates, [12][13][14] who advocated that SVHs should be greater than 5 mm to be integrated into the drainage system, reported in their latest study that they integrated SVHs ≥ 4 mm into the drainage system. Most the integration models aimed at developing a wide ostium anastomosis tolerating compression are made of allogenic grafts or artificial graft materials.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous grafts should be preserved by cryopreservation, and no proliferation in cultures should form from the graft material before using the graft. 1,6,12 The recipient left portal vein, the paraumbilical vein, and the vena saphena magna may be used as an autologous vessel Saphenous vein and iliac artery graft was used for creating the common-large opening models. graft.…”
Section: Discussionmentioning
confidence: 99%
“…Although some centers advocate venoplasty of the right hepatic vein (RHV) and the middle hepatic vein (MHV) into a common venous channel, which is then anastomosed directly to a newly created opening on the anterior wall of the inferior vena cava (IVC), 2 others use a variety of extension grafts on the veins draining segments V and VIII, which are then anastomosed to the IVC. 3,4 We use the MHV stump or a length of the MHV from the recipient's liver and perform a direct anastomosis with the MHV of the graft without the use of any extension. We report this technique for anterior sector venous outflow reconstruction, which we have successfully employed at our institution for 78 right lobe LDLT procedures.…”
mentioning
confidence: 99%
“…Various reconstruction techniques have been reported using autologous vein grafts such as the greater saphenous vein, 2 the left portal vein (PV), 3 or the paraumbilical vein. 4 Moreover, some techniques have been reported using cryopreserved veins 5 or arteries 6 ; however, the availability of such vascular grafts is extremely limited.…”
mentioning
confidence: 99%
“…The Model for End-Stage Liver Disease score was 9. Imaging studies revealed severe liver cirrhosis with 3 hypervascular nodules (maximum size, 2.3 cm) in segments 8,6, and 7 of the liver, which were compatible with hepatocellular carcinomas. An LDLT was indicated because of the expected poor prognosis with conventional therapeutic modality.…”
mentioning
confidence: 99%